Analisis Problem Solving Juvenile Delinquency Remaja Kokoda Belakang Diklat KM 8 Kota Sorong. - Rabrusun, Fatima; Sari, Fatma (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
The Problem of Juvenile Delinquency for Teenagers Kokoda is behind the KM Training. 8 Sorong City with a problem solving method approach in solving social problems. And research methods using qualitative. Data collection techniques with observation, interviews and documentation. The technical analysis of the data collected in this study, including data reduction, data presentation and verification or drawing conclusions, was re-examined to determine the completeness of the data obtained. The factors that influence the occurrence of Juvenile Delinquency behavior, namely, teenagers have curiosity and originate from promiscuity. As for the inputs provided by the Sorong City Government, traditional leaders and community leaders to be used as a solution by the Malaimsimsa District, the first places more emphasis on the spiritual aspect, the second is that forming the character of children starts from the family environment and the third is that young people must find jobs that are commensurate and must be occupied so that These social behaviors disappear with time. Of these three factors, it is not a guarantee and a solution in dealing with the juvenile delinquency behavior of Kokoda teenagers behind training. KM 8 Sorong City. So that this thesis will be used as a reference for creating a coaching program for the Kokoda youth behind the KM 8 Education and Training Center, Sorong City.